Double down - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series), 2016)
Greg Heffley records his humorous misadventures for the months of October and November in his diary, describing the secret film crew documenting his life, his fateful Halloween party, troubles at school, and the horror movie he films with gummy worms in order to get rich.